Google Earth forensics : using Google Earth geo-location in digital forensic investigations - Harrington, Michael (Writer on mobile device forensics); Cross, Michael, 1965- (Elsevier, 2014)
"Google Earth Forensics" is the first book to explain how to use Google Earth in digital forensic investigations. As mobile computing devices become increasingly prevalent and powerful, they are becoming more useful in the field of law enforcement investigations and forensics. Of all the widely used mobile applications, none have more potential for helping solve crimes than those with geo-location tools. This book teaches readers how to leverage Google's free tool to craft compelling location-based evidence for use in investigations and in the courtroom. It shows how to extract location-based data, how to explain the data in contextual, meaningful, and easy-to-understand ways, and how to display the data as evidence using compelling audiovisual tools.